PENGEMBALIAN UANG BELANJA KONSUMEN DIGANTI PERMEN PADA SAAT TRANSAKSI - Laras Sati; Felisa Prilly Priscilla Santoso; Gamas Andika Wijaya (JISOS: JURNAL ILMU SOSIAL, 2022)
What we often experience when shopping at both supermarkets and minimarkets is that there is often a transfer of consumer change in other forms, such as offers of donations made unilaterally by business actors and some even return them in other forms such as candy. In this case, many consumers complain not because of the large nominal amount of money but rather the mentality of business actors who are less able to capture the psychological burden of consumers. In this paper, the author seeks to reveal how the phenomenon of money transfer practices in several cities in Indonesia and how to resolve disputes over money transfer cases in several cities in Indonesia